Niger : Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
In the social sectors, encouraging results were obtained in education. The Ten-Year Education Program was finalized, creating a solid basis for the implementation of actions in this sector. According to the most recent estimates, the basic enrolment rate was 41.7 percent in 2002 compared with 37.3 percent in 2001. These results are owing to the efforts of the government in recruiting volunteer teachers and building and equipping of classrooms. The government also adopted a national policy for higher education.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet